PERANCANGAN SISTEM RESERVASI DAN PROMOSI HOTEL BERBASIS WEBSITE - Vivi Sahfitri (Jurnal Informatika, 2020)
The rapid development of information technology, triggering every area of life must be able to innovate so as not to lag or even disappear. One of the areas that has been utilizing many technologies is the economic and business areas. One of the businesses that is currently growing is the hospitality business. Regional potential in Indonesia that provides many benefits for tourists ranging from sport or recreation to make the business of hospitality become a promising effort. The number of hotels established, making business competition increasingly higher. facilities, promotion, service and convenience in obtaining information and transaction into a factor that can impact the business progress of the hotel. Fast information service especially for reservation is indispensable. This research aims to design a reservation and promotion system in a Web-based hospitality business.  The methods used in this research are the Software Development Life Cycle (SDLC) method as well as system design using Unified Modelling Language (UML).  This research generates a prototype reservation system and promotion of a website-based hospitality business that can be implemented to build information systems and can then be used to facilitate the dissemination of information/hotel promotion and facilitate consumers to make reservations online